Edukasi perkembangan sosioemosional bagi guru PAUD untuk mendukung kesehatan mental anak usia dini - Sayang Ajeng Mardhiyah; Hertanti Indah Lestari; Rosada Dwi Iswari; Yudianita Kesuma (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2026)
Socio-emotional development education for early childhood educators to support the mental health of young children. The socio-emotional development of young children is a crucial foundation for mental health and psychosocial adaptation. The early childhood education (PAUD) environment plays a strategic role in supporting this development through teacher-child interactions; however, teachers’ limited understanding of socio-emotional development remains a challenge in implementing learning approaches that support children’s mental health. This activity aims to enhance early childhood education teachers’ knowledge of children’s socioemotional development through educational materials such as videos, brochures, and interactive discussions. Participants consisted of 42 early childhood education teachers in Palembang City who took pre- and post-tests. The results showed an increase in knowledge from an average of 71.29 to 80.55, with a significant difference (t = 3.55; p = 0.001). Participant feedback also indicated improved understanding of the importance of children’s socio-emotional development, as well as a need for more practical follow-up training. These findings suggest that social-emotional education for early childhood education teachers has the potential to serve as a strategy in supporting the promotion of mental health in young children.